Contact Resistance of Metal-CNT Contacts in Field Effect Based Sensors - Alabsi, S.S. (Institute of Electrical and Electronics Engineers Inc., 2021)
Contact engineering is a very crucial area of sensor development. This is especially true when dealing with devices at the very small micro and nano scale. Field effect-based sensors implementing nanodevices as channel material are amenable to extreme device miniaturization. Semiconducting carbon nanotubes (sc-CNTs) are exceptionally promising for FET-channel integration to replace bulky silicon technology beyond the dimensions of the short channel effects for their ID ultrathin structure, and superior mechanical and electronic features. However, the inhomogeneous contact between metal electrodes and the sc-CNT is amounting at relatively high contact resistance. In this paper, the effect of variation of certain physical parameters on electronic features was mathematically investigated using Y-Function Method (YFM) equations. Two physical parameters; CNT diameter and contact length, were varied in a range of set values. Results show that lower band gap energy and threshold voltage are obtained with larger CNT diameters, while increasing contact length have a significant reduction effect on contact resistance. In addition, the effect of contact resistance on sensor's performance in terms of drain current and the transconductance was also demonstrated. Â© 2021 IEEE.